Neuroprotective Effects of a Small Mitochondrially-Targeted Tetrapeptide Elamipretide in Neurodegeneration - Nhu, Nguyen Thanh; Xiao, Shu-Yun; Liu, Yijie; Kumar, V. Bharath; Cui, Zhen-Yang; Lee, Shin-Da (Frontiers in Integrative Neuroscience, 2022)
Neural mitochondrial dysfunction, neural oxidative stress, chronic neuroinflammation, toxic protein accumulation, and neural apoptosis are common causes of neurodegeneration. Elamipretide, a small mitochondrially-targeted tetrapeptide, exhibits therapeutic effects and safety in several mitochondria-related diseases. In neurodegeneration, extensive studies have shown that elamipretide enhanced mitochondrial respiration, activated neural mitochondrial biogenesis via mitochondrial biogenesis regulators (PCG-1α and TFAM) and the translocate factors (TOM-20), enhanced mitochondrial fusion (MNF-1, MNF-2, and OPA1), inhibited mitochondrial fission (Fis-1 and Drp-1), as well as increased mitophagy (autophagy of mitochondria). In addition, elamipretide has been shown to attenuate neural oxidative stress (hydrogen peroxide, lipid peroxidation, and ROS), neuroinflammation (TNF, IL-6, COX-2, iNOS, NLRP3, cleaved caspase-1, IL-1β, and IL-18), and toxic protein accumulation (Aβ). Consequently, elamipretide could prevent neural apoptosis (cytochrome c, Bax, caspase 9, and caspase 3) and enhance neural pro-survival (Bcl2, BDNF, and TrkB) in neurodegeneration. These findings suggest that elamipretide may prevent the progressive development of neurodegenerative diseases via enhancing mitochondrial respiration, mitochondrial biogenesis, mitochondrial fusion, and neural pro-survival pathway, as well as inhibiting mitochondrial fission, oxidative stress, neuroinflammation, toxic protein accumulation, and neural apoptosis. Elamipretide or mitochondrially-targeted peptide might be a targeted agent to attenuate neurodegenerative progression.